Draft Genome Sequences of Dickeya sp. Isolates B16 (NIB Z 2098) and S1 (NIB Z 2099) Causing Soft Rot of Phalaenopsis Orchids - Alic, Spela; Naglic, Tina; Llop, Pablo; Toplak, Natasa; Koren, Simon; Ravnikar, Maja; Dreo, Tanja (American Society for Microbiology, 2022)
The genus Dickeya contains bacteria causing soft rot of economically important crops and ornamental plants. Here, we report the draft genome sequences of two Dickeya sp. isolates from rotted leaves of Phalaenopsis orchids